Exploring peri-urban dynamism in India: Evidence from Kolkata Metropolis - Dinabandhu Mondal; Anuradha Banerjee (Journal of Urban Management, 2021)
Peri-urbanisation around metropolitan cities of India has been an emerging and apparent phenomenon in the last few decades. The peri-urban spaces, which are characterised by co-existence of urban and rural elements, are very dynamic in nature and undergoing continuous changes with regards to land use, population characteristics, and social systems. They are in fact considered as "regions of change". This paper tries to explore how do the processes of peri-urbanisation around cities instigate changes at the periphery of cities and what are the implications of these changes on the economic condition of peri-urban residents? It is observed that although the transitory spaces usually represent a spatial continuum between urban and rural counterparts, there are some instances where the continuum breaks. These spaces are experiencing rapid population growth, while stagnant or negative growth is observed in the urban core. Land use changes are very prominent in these transitional spaces as the built-up area is unprecedentedly increasing due to urban expansion. The study finds that peri-urbanisation brings unequal benefits for its residents; it opens new employment opportunities in emerging non-agricultural sectors, but at the same time it also aggravates gender disparity in work.
Keywords: 710; Peri-urbanisation; Dynamism; Population growth; Land use changes; Employment; Kolkata